Doskonalenie zarządzania kapitałem intelektualnym w małym przedsiębiorstwie - propozycja rozwiązań - Sokołowska, Agnieszka (Improvement of Intellectual Capital Management - Solutions Proposals, 2008)
The author presents conditions and symptoms of intellectual capital management in small business. Moreover, the author proposes ways of improvement of identification, measurement, creation and development of intellectual capital in small business, with regard to specificity of business activity. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 266-278